Exploring the Nature of Shifts in Learner Autonomy and Teacher Autonomy in an Online EFL Class in Turkiye: A Case Study - Demir, Selin; Mede, Enisa (Institut Agama Islam Negeri Madura, 2024)
The need to understand the manifestation of learner autonomy in the online learning environment and its challenges in the classroom is increasing with the rise of online education. Although learner autonomy (LA) is increasingly important in language education, there is less knowledge about teachers' and students' comprehension and use of this concept. In order to address this lack of information, a case study was conducted to explore the perceptions of teachers and learners about learner autonomy in an online environment. The study's data sources include reflective journals, lesson observations, and focus group interviews. The study, conducted at a Turkish foundation university, identified a variety of control shifts in the courses. This research explored the concept of learner autonomy in the context of online language training. The findings indicated that students had a favorable perception of online learning, highlighting its flexibility, ease, and ability to establish individual standards. Nevertheless, there was a noticeable difference between how they perceived autonomy and how it was really put into practice, typically favoring a teacher-centered approach. Several factors that impacted learner autonomy in online learning were recognized, such as the need for autonomy, inadequate information, and a transition toward teacher-centric approaches. The research emphasized the significance of aspects such as guidance and support systems, adaptability, student motivation, customized learning speed, and communication technologies.